Pelatihan Keterampilan Menjaga Kesehatan Mental Melalui Strategi Psiko-Edukatif Remaja Panti Asuhan Putri Aisyiah II Kadipiro, Banjarsari, Surakarta - Hera Heru Sri Suryanti; Lydia Ersta Kusumaningtyas (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
The purpose of the community service activity with the theme Training in skills to maintain mental health through psychoeducational strategies for adolescents at the Putri Aisyiah II Kadipiro Orphanage, Banjarsari, Surakarta is to equip knowledge and skills to maintain mental health so that they live happily. The target of this community service activity is the realization of mental health skills guidelines that can be used by young members of the Kadipiro Aisyiah II Putri Orphanage, Banjarsari, Surakarta, to realize and maintain a healthy mentality so that they become productive members of society. This community service is carried out by applying the Brenstorming method, Lecture method, Question and answer method, Exercise method and Case studies so that the material is easily accepted by members. The activity was carried out for one month with a frequency of once a week, the place of implementation was at the Kadipiro Aisyiah II Putri Orphanage, Banjarsari, Surakarta. Through this activity the members have the knowledge and skills to maintain mental health, so that they can strengthen the young girls who are members of the orphanage and ultimately the young women become strong and productive members of society. The output of this community service is the publication of scientific articles in journals with ISSN.